Non-Shia practices of Muḥarram in South Asia and the diaspora: beyond mourning - Sohoni, Pushkar; Tschacher, Torsten (Routledge South Asian religion series, 2022)
Ḥusayn's Hindu defenders / Tryna Lyons -- An ethnographic exploration of Muharram(s) in Pune, Maharashtra / Deepra Dandekar -- Visual language of piety and power: Ta'ziahs and temples in the western Deccan / Pushkar Sohoni -- The idea of religion and the criminalization of Muharram in the Straits Settlements, 1830-1870 / Torsten Tschacher -- Contestation and rransformation : Muharram practices among Sunni Muslims in South Africa, 1860-2020 / Goolam Vahed -- It ain't religion, it's just culture, man! Muharram controversies in the Indo-Caribbean diaspora / Frank J. Korom.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Muharram; Südasien